Satisfação dos usuários do Portal de Periódicos da CAPES - Juliana Lopes de Almeida Souza (2011)
This dissertation statistically evaluates the CAPES Digital Library of Scientific Journals´ User Satisfaction questionnaire. The investigated sample was composed by 930 researchers, who were selected when limiting the areas from 17 federal universities, in five regions. It was used quantitative methodology with the collection of some qualitative data. The undertaken research was characteristically exploratory and descriptive. The study examined, by using descriptive statistics, the degree of user satisfaction within areas of Biological Sciences, Linguistics, Literature and Arts, and Humanities and their sub-areas of knowledge. The results show that the majority (52%) have some difficulty in using CAPES Journal Portal. The ANOVA test compared answers and revealed through the Tukey test, that the Biological Sciences area is the most satisfactory in relation to the general reaction to the visual design, content, and access to the journals of CAPES Digital Library of Scientific Journals. This research concluded that the CB area is the most satisfied among the areas studied, because it showed statistically significant differences in relation to the general reaction to the visual design, access and content of the portal with the other two areas investigated. The data indicated no concentration of users satisfied or dissatisfied in a particular region of Brazil. Particular attention deserves the field of Linguistics, Arts and Letters in less than half (45%) of the researchers are successful in the search to look for a journal. The data also indicate that lack of knowledge of other languages and even the need for training does not pose major problems for 76% of respondents. The three areas indicated as the main reason for not achieving success: the unavailability of the journal, or a particular issue in the Portal. From the qualitative data analysis, this dissatisfaction was confirmed among the 56 researchers, who detailed the reasons for the failure in obtaining the periodical. The users´satisfaction was an assessement tool and an indicator that the Portal was fulfilling its role as being a way of meeting the need for information. The data of this research indicate as the main failure in meeting the researchers´needs, the unvailability of the journals.